PSYCHIATRIC/BEHAVIOURAL EVENTS WITH PERAMPANEL TREATMENT FOR PGTCS. Issue 12 (15th November 2016) - Dobrinsky, Cindy; Ettinger, Alan; Rosenfeld, William; Williams, Betsy; Laurenza, Antonio; Yang, Haichen; Patten, Anna; Bibbiani, Francesco
Abstract : Purpose: To review psychiatric and behavioural events in a study conducted to evaluate the efficacy and safety of adjunctive perampanel in patients with uncontrolled primary generalised tonic-clonic seizures (PGTCS). Method: Following baseline (4 or 8 weeks), patients aged ≥12 years were randomised to double-blind treatment with perampanel or placebo (titration 4 weeks; maintenance 13 weeks; maximum dose 8 mg). Treatment-emergent adverse events (TEAEs) were evaluated using MedDRA search terms for psychiatric disorders and MedDRA SMQs for hostility/aggression-related events. Results: In the Safety Analysis Set (perampanel n=81; placebo n=82), psychiatric TEAEs occurred in 20 (24.7%) perampanel- and 16 (19.5%) placebo-treated patients. Most TEAEs were of mild or moderate intensity. Frequency of TEAEs related to hostility/aggression was 18.5% for perampanel and 4.9% for placebo, largely due to a higher rate of irritability with perampanel (11.1%) versus placebo (2.4%). Incidences of serious adverse events and discontinuations due to TEAEs related to hostility/aggression for perampanel versus placebo were 1.2% versus 0% and 3.7% versus 1.2%, respectively. Conclusion: Consistent with results from Phase III trials in partial epilepsy, hostility/aggression-related TEAEs occurred at a higher rate in perampanel-treated patients with PGTCS than in those treated with placebo, driven mainly by irritability. Supported by Eisai Inc.